2002
DOI: 10.1098/rspb.2002.2107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of progressive hypoxia on school structure and dynamics in Atlantic herringClupea harengus

Abstract: The effect of progressive hypoxia on the structure and dynamics of herring (Clupea harengus) schools in laboratory conditions was investigated. The length, width and depth of schools of about 20 individuals were measured from video recordings to test the hypothesis that during hypoxia fish schools change their shape and volume. School shape (calculated as the ratios of length/depth, width/depth and length/width) did not change significantly during hypoxia. School length, width, depth, area and volume were all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 42 publications
(96 reference statements)
4
64
1
Order By: Relevance
“…These results are in agreement with other studies of pelagic species that have demonstrated vertical avoidance of low-oxygen bottom water (Aku et al 1997, Keister et al 2000, Wanink et al 2001, Prince & Goodyear 2006. Additional effects of vertical avoidance behavior have also been demonstrated, including disruption of diel patterns of vertical migration (Schurmann et al 1998), altered schooling behavior (Domenici et al 2000(Domenici et al , 2002, and changes in patch structure in overlying normoxic waters (Taylor & Rand 2003). Further research is needed to determine the consequences of vertical avoidance of bottom water hypoxia for these other aspects of spatial distribution for fishes in the Gulf of Mexico.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with other studies of pelagic species that have demonstrated vertical avoidance of low-oxygen bottom water (Aku et al 1997, Keister et al 2000, Wanink et al 2001, Prince & Goodyear 2006. Additional effects of vertical avoidance behavior have also been demonstrated, including disruption of diel patterns of vertical migration (Schurmann et al 1998), altered schooling behavior (Domenici et al 2000(Domenici et al , 2002, and changes in patch structure in overlying normoxic waters (Taylor & Rand 2003). Further research is needed to determine the consequences of vertical avoidance of bottom water hypoxia for these other aspects of spatial distribution for fishes in the Gulf of Mexico.…”
Section: Discussionsupporting
confidence: 82%
“…Although positional preferences have been observed in schools in relation to the physiological state of each individual (e.g. hunger level, Krause et al 1998), schooling is a dynamic behaviour, and most fish continuously change positions from trailing to leading (Krause 1993(Krause , 1994Domenici et al 2002). A relatively constant reshuffling rate was found in schools of herring Clupea harengus which decreased when fish were exposed to hypoxia (Domenici et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…hunger level, Krause et al 1998), schooling is a dynamic behaviour, and most fish continuously change positions from trailing to leading (Krause 1993(Krause , 1994Domenici et al 2002). A relatively constant reshuffling rate was found in schools of herring Clupea harengus which decreased when fish were exposed to hypoxia (Domenici et al 2002). For all individuals to take advantage of schooling, sufficient shuffling should occur such that each fish can spend a relatively large proportion of the time in a trailing position (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As the dimensions of schools increase, O-turning, used in changing position within the school, is suppressed while shuffling rate remains constant. This behaviour results in increased overtaking of position within the school, perhaps leading to an increase in overall energy expenditure (Domenici, 2002). The increase in spatial extent of the school leads to a larger inter-individual distance causing lower communication and higher vulnerability to predators.…”
Section: Schoolingmentioning
confidence: 99%